The Effect of Health Expenditure, Education Expenditure, and Poverty on the Human Development Index in Lampung Province - Berutu, Saiful Ragatna; Seprianti, Viola Ditya; Tanjung, Ahmad Albar; Sukardi, Sukardi (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
The Human Development Index can be used as an indicator of successful development in a country or region. In 2023, Lampung Province's Human Development Index in 2023 amounted to 72.48 and was the lowest in Sumatra Island. This study aims to determine how much the speed of convergence of the Human Development Index between districts/cities in Lampung Province and also to determine how much influence the variables of Health Expenditure, Education Expenditure, and Poverty affect the Human Development Index in Lampung Province in the short and long term. The study used secondary data on Health Expenditure, Education Expenditure, Poverty, and Human Development Index in 13 districts/cities in Lampung Province from 2014 to 2022. The research method used is dynamic panel data regression using the Sys-GMM model. The results showed that the Human Development Index gap between districts/cities in Lampung Province decreased by 54.49% per year. The elasticity of the short-term effects of Health Expenditure, Education Expenditure, and Poverty on the Human Development Index is 9.27%, -1.52%, and -2.41%, respectively. In the long run, health expenditure, education expenditure, and poverty affect the Human Development Index by 20.38%, -3.35%, and -5.30%, respectively. Therefore, the government should continue programs in the health sector, evaluate spending in the education sector, and create poverty alleviation programs that have a significant impact.